THE EFFECT OF LACTATION MASSAGE ON INCREASING BREAST MILK PRODUCTION IN BREASTFEEDING MOTHERS - Ratih Kumala Dewi; Rifa Yanti; Fajar Sari Tanberika; Rika Ruspita (Academic Solution Publisher, 2026)
Lactation massage is believed to stimulate increased levels of the hormones prolactin and oxytocin. The aim of this study was to determine the effect of lactation massage on breast milk production in breastfeeding mothers. This study was quantitative with a quasi-experimental design. It was conducted from October to November 2025. The sample size was 16 pregnant women. Data analysis was performed using computerized univariate and bivariate tests using the Wilcoxon test. Breast milk production was 27.19 ml with a standard deviation of 4.820. After being given lactation massage, the average breast milk production changed to 53.75 ml with a standard deviation of 6.708. There is an effect of lactation massage on breast milk production in breastfeeding mothers at the Kedaburapat Community Health Center, Rangsang Pesisir District, Meranti Islands Regency (p=0.000). It is suggested that health workers provide additional health education about the effect of lactation massage on breast milk production among breastfeeding mothers so that breastfeeding mothers not only receive health services but also gain knowledge or health education regarding lactation massage.